Efficacy of Dry Needling and Intramuscular Dry Needling Stimulation on Quadratus Lumborum in Patients with Mechanical Low Back Pain - Gerald Edwin Raj; Vinodhkumar Ramalingam; M. K. Franklin Shaju (Фізична реабілітація та рекреаційно-оздоровчі технології)
Low back pain (LBP) is characterized by pain or discomfort in the lower back, often accompanied by decreased in lateral flexion range of motion. The average lifetime incidence of LBP is as high as 84%, with approximately 23% of individuals experiencing chronic pain.